Safety assessment of the substance [3‐(2, 3‐epoxypropoxy)propyl]trimethoxy silane, for use in food contact materials. (27th October 2017) - ; Silano, Vittorio; Bolognesi, Claudia; Chipman, Kevin; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; Kärenlampi, Sirpa; Mennes, Wim; et al.
Abstract: This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety evaluation of [3‐(2, 3‐epoxypropoxy)propyl]trimethoxy silane as a component for sizing glass fibres used for manufacturing glass‐fibre‐reinforced plastics. The substance is typically applied at up to around 0.2% related to the final plastic. The resulting food contact materials are intended for various scenarios of use, i.e. long‐term contact at ambient temperature (e.g. storage tanks) or short‐term contact at elevated temperatures (e.g. kitchen utensils). In extracts of treated fibres, neither the substance was detectable at 10 μg/kg fibre nor its hydrolysis product and oligomers at 60 μg/kg fibre. Based on the detection limits, modelling for the plastics and scenarios of intended use resulted in maximum migrations of 0.05 μg/kg food for the substance and 0.15 μg/kg food for the sum of the reaction products. The Panel concludes that the substance has a genotoxic potential. This may also apply to some of its reaction products which contain the epoxy function. However, due to the very low exposure, if any, [3‐(2, 3‐epoxypropoxy)propyl]trimethoxy silane does not raise safety concern if used as a component of sizing agents to treat glass fibres imbedded into low diffusivity plastics (polyethylene terephthalate, polycarbonate, polybutylene terephthalate, thermoset polyesters and epoxy bisphenol vinylester) in contact with all foodstuffs. In addition, the residues in the treated glass fibres must not be detectable at 10 μg/kg for the substance and 60 μg/kg for each of the reaction products (hydrolysed monomers and epoxy‐containing cyclic dimer, trimer and tetramer).